Multidisciplinary Perspective Intervention With Community Involvement to Decrease Antibiotic Sales in Village Groceries in Thailand. (March 2015) - Arparsrithongsagul, Somsak; Kulsomboon, Vithaya; Zuckerman, Ilene H.
In Thailand, antibiotics are rampantly available in village groceries, despite the fact that it is illegal to sell antibiotics without a pharmacy license. This study implemented a multidisciplinary perspectives intervention with community involvement (MPI&CI), which was developed based on information obtained from focus groups that included multidisciplinary stakeholders. Community leaders in the intervention group were trained to implement MPI&CI in their villages. A quasi-experiment with a pretest–posttest design was conducted. Data were collected from 20 villages in Mahasarakham Province (intervention group) along with another 20 villages (comparison group). Using a generalized linear mixed model Poisson regression with repeated measures, groceries in the intervention group had 87% fewer antibiotics available at postintervention compared with preintervention (relative rate = 0.13; 95% confidence interval = 0.07-0.23), whereas the control group had only an 8% reduction in antibiotic availability (relative rate = 0.92; 95% confidence interval = 0.88-0.97) between the 2 time periods. Further study should be made to assess the sustainability and long-term effectiveness of MPI&CI.